Development of an instructional package for the promotion of universal human values and soft skills among higher secondary school students - Baby A (N S S Training College Ottapalam, University of Calicut, 2025)
The study aimed to prepare, design validate and evaluate an Instructional Package grounded in the philosophical and practical foundation of Ashtanga Yoga, and humanistic psychology. The package integrated the principles of Yama and Niyama principles that strengthen Universal Human Values, soft skills that strengthen student’s awareness, adaptability, assertive, conflict resolution, empathy, communication and leadership and responsive behavior. The sample size was 112 higher secondary school students of H S S Keralasseri. 56 students for experimental group and 56 students from control group from two classes. A non- equivalent quasi-experimental design was used for the study. The experimental group received intervention package while the control group didn’t get any treatment. The tools were standardized and the data were collected by the researcher under the guidance of supervising teacher. Statistical techniques used in this study were independent t test, paired sample t test, and ANCOVA and examined the effectiveness of the intervention. The findings revealed that there exists a significant difference between the experimental and control group at 0.05 level of significance. The effect size also indicated the Instructional Package was remarkably effective to promote Universal Human Values and Soft Skills. So the Instructional Package was effective in enhancing Universal Human Values and Soft Skills. The study concluded that the Instructional Package significantly contributed to the promotion of Universal Human Values and soft skills among higher secondary school students.
Keywords: Instructional Package; Universal Human Values; Soft Skills.